2023
DOI: 10.1021/acs.jafc.3c03806
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Germ-Derived Peptide Alleviates Dextran Sulfate Sodium-Induced Colitis in Mice

Fang Wang,
Yuanrong Chen,
Kiyoshi Itagaki
et al.

Abstract: This study explores the protective properties and potential mechanisms of wheat-germ-derived peptide APEPEPAF (APE) against ulcerative colitis. Colitis mice induced by dextran sulfate sodium (DSS) were used as the animal model. The results showed that the APE peptide could alleviate colitis symptoms including weight loss, colon shortening, and histopathological changes. This peptide attenuated the generation of inflammatory cytokines by inhibiting the phosphorylation of protein kinase PKCζ (Thr410) and NF-κB t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…In addition, rice protein peptides can alleviate DSS-induced colitis by modulating intestinal flora and modulating Keap1-Nrf2 [23,48]. In addition, prophylactic supplementation with wheat germ-derived hybrid peptides (520 mg/kg), as well as APEPEPAF (50 mg/kg), was able to alleviate DSS-induced colitis by inhibiting the NF-κB pathway and ameliorating gut microbiota disturbances [49]. These studies suggest that food-borne peptides have a greater potential for use as dietary supplements in the prevention of UC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rice protein peptides can alleviate DSS-induced colitis by modulating intestinal flora and modulating Keap1-Nrf2 [23,48]. In addition, prophylactic supplementation with wheat germ-derived hybrid peptides (520 mg/kg), as well as APEPEPAF (50 mg/kg), was able to alleviate DSS-induced colitis by inhibiting the NF-κB pathway and ameliorating gut microbiota disturbances [49]. These studies suggest that food-borne peptides have a greater potential for use as dietary supplements in the prevention of UC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a variety of agents that have efficacy in IBD are known to inhibit the NF-κB pathway [33,[89][90][91]. These include some peptide-based drugs, such as Cathelicidin-BF, WFNNAGP, LP-5, pep-1, APE, and LL-37-Tα1 [92][93][94][95][96][97]. Immunohistochemical examination of the colon tissue showed that chensinin-1b effectively suppressed the expression of NF-κB p65.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The APEPEPAF peptide derived from wheat germ peptides has been shown to protect against colitis by restoring the damaged mucus barrier and inhibiting the activation of inflammatory signaling. 13 However, the bioactive peptides of wheat peptide still have great potential to be explored.…”
Section: Introductionmentioning
confidence: 99%